ENGLISH TEACHING CHALLENGES WITH STRONG LOCAL LANGUAGES IN REMOTE AREAS : AN ETHNOGRAPHIC STUDY - Dwi Husnul Khatima; Sukardi Weda; Muhalim Muhalim; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This ethnographic study explores the challenges faced by English language teachers in remote areas with strong local language cultures, with a focus on SMPN 1 Kabangka, located in Muna Regency, Southeast Sulawesi. The study is guided by Ethnolinguistic Identity Theory, which emphasizes the role of language in shaping group identity and social belonging. In regions where a local language—such as Muna—is strongly embedded in daily communication, the introduction of English in the classroom creates both linguistic and cultural tensions.Using a qualitative ethnographic approach, data were collected through classroom observations and semi-structured interviews with three English teachers. The findings reveal that the dominance of the Muna language significantly affects instructional delivery, student engagement, and the development of English language skills. Teachers often resort to code-switching between English, Indonesian, and Muna to facilitate comprehension, but this strategy reduces consistent exposure to English and can impede learners’ language acquisition.Additional challenges include limited access to teaching resources, lack of professional development tailored to multilingual contexts, and the misalignment between the national curriculum and local linguistic realities. Students’ low motivation to learn English is also linked to their stronger identification with the local language, reinforcing the relevance of Ethnolinguistic Identity Theory in this context. Despite these obstacles, teachers demonstrate resilience and adaptability by incorporating local culture into English instruction, simplifying materials, and building rapport with students.